1996
DOI: 10.1046/j.1365-3091.1996.d01-8.x
|View full text |Cite
|
Sign up to set email alerts
|

Holocene Saharan dust deposition on the Cape Verde Islands: sedimentological and Nd‐Sr isotopic evidence

Abstract: Holocene aeolian silts deposited on the Cape Verde Islands provide information about the origin of African palaeodusts that have fallen on the north‐eastern Atlantic ocean over the last 10 000 years. Sedimentological composition indicates that most of these aeolian silts are unquestionably of continental origin. Their Sr and Nd isotopic composition identifies a Saharan origin‐suggesting transport by Harmattan winds. We estimate that Saharan dust comprises 75–95% of material in these Holocene silts, the rest co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 20 publications
7
40
0
Order By: Relevance
“…These authors showed that the structural water loss for 17 soil samples ranges from 0.56 to 2.45 % at 550 • C. This is consistent with the mass loss results obtained for the Douz soil which contains a significant proportion of quartz and calcite (Lafon et al, 2014). The larger mass loss observed for the Cape Verde soil can be partly due to its composition of quartz, potassic feldspars and an assemblage of illite-kaolinite-chlorite (Rognon et al, 1996;Desboeufs et al, 1999). The larger loss on ignition observed for the atmospheric deposition suggests a higher fraction of volatile compounds in the Frioul samples than in the tested soils.…”
Section: Weighing and Ignition Protocolsupporting
confidence: 77%
“…These authors showed that the structural water loss for 17 soil samples ranges from 0.56 to 2.45 % at 550 • C. This is consistent with the mass loss results obtained for the Douz soil which contains a significant proportion of quartz and calcite (Lafon et al, 2014). The larger mass loss observed for the Cape Verde soil can be partly due to its composition of quartz, potassic feldspars and an assemblage of illite-kaolinite-chlorite (Rognon et al, 1996;Desboeufs et al, 1999). The larger loss on ignition observed for the atmospheric deposition suggests a higher fraction of volatile compounds in the Frioul samples than in the tested soils.…”
Section: Weighing and Ignition Protocolsupporting
confidence: 77%
“…We use the Nd isotope signature of peat to decipher between local and distal sources (such as in Le Roux et al, 2012). The observed eNd variability (À13 to À9) in Misten peat samples is interpreted as a mixing between dust sources (Table 3) from local (Early Cambrian shales = À11.3, André et al, 1986; Early Cambrian phyllades = À10.8 and mean Paleozoic shales = À12.2, Linnemann et al, 2012), regional soils (mean European crust = À10.8, Michard et al, 1985; mean European loess = À11.6, data from Gallet et al, 1998) and desert particles (mean Saharan airbornes = À12.9 -data from Goldstein et al, 1984;Grousset et al, 1988a,b;Colin, 1993;Henry et al, 1994;Rognon et al, 1996). The eNd variability is further compared with the humification degree to evaluate the local relative humidity conditions (Fig.…”
Section: Climate-related Dust Record In Misten Peat Bog Over the Histmentioning
confidence: 99%
“…The precipitation Sr flux was based on the precipitation Ca flux and the measured Ca/Sr ratio of precipitation. 87 Sr/ 86 Sr ratios of streamwater, precipitation, and bedrock were directly measured, and the 87 Sr/ 86 Sr ratio of Saharan dust was taken from previous studies of airborne dust and ocean sediment from the tropical North Atlantic (Biscaye et al 1974;Grousset et al 1988;Grousset et al 1998;Grousset et al 1992;Rognon et al 1996). Specifically, the Sr isotope approach calculates the dust weathering flux, setting a minimum lower bound on the dust deposition flux.…”
Section: Site Descriptionmentioning
confidence: 99%